Ce are turcul cu porcul de nu-l mănâncă? Reprezentări ale turcului în mediul rural românesc (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
This research wish to point the thesis which claims that any community needs a scheme of "performance" which includes the whole community of "us" and "all of them", or "others". The ethnic affiliation of "other" is determined by series of concrete and particular situations. These situations depends on proximity or remote of certain sources of "alterity" pressure. The passage of time created for South-East Europe an image of a Turk, image which played an important role in the above mentioned - source of pressure. It is understandable, in this order of thinking, why the image of Turk, in frames and situations which at first sight seems to be inadequate, is present. Like any other image, the image of the fantastic-Turk (the Turk with tail or its animal hypostasis) or the devil Turk (Satane's ally or deputy) has its competences in the consensual peasant world. This image had functions - of an educational system, an etiology, a way of self-knowing through all kinds of mirrors of alterity.